Development of the Cost-Based Model for Monitoring the Lifetime of the Earth Moving Machines - Ugljesa Bugaric; Milos Tanasijevic; Stevan Djenadic; Dragan Ignjatovic; Ivan Jankovic (Machines, 2022)
This paper presents the model for the identification of reference points on the lifetime curve of engineering systems. This curve commonly represents the increase and decline of failure in relation to time. A direct correlation between failure rate and costs is assumed in this paper, therefore, statistical and empirical analysis of costs provided reference points. This approach is used for positioning stages of the engineering system’s lifetime with a minimal number of failures and costs, regardless of whether these are acceptable or not. The following three stages are usually identified: the beginning, the stationary part and the end of life. The boundaries between them are recognized on the basis of minimum total lifetime costs and on economic lifetime costs. Model is tested on the dozers, machines frequently used in the mining industry for the earthmoving operations, and which are characterized by high operating and maintenance costs.